Unexpected absence of island endemics: Long-distance dispersal in higher latitude sub-Antarctic Siphonaria (Gastropoda: Euthyneura) species - Gonzalez-Wevar, Claudio A.; Segovia, Nicolas I.; Rosenfeld, Sebastian; Ojeda Villarroel, Jaime Andrés; Hune, Mathias; Naretto, Javier; Saucede, Thomas; Brickle, Paul; Morley, Simon; Feral, Jean-Pierre; Spencer, Hamish G.; Poulin, Elie (My University, 2018)
Aim: We assess biogeographical patterns, population structure and the range of species in the pulmonate genus Siphonaria across the sub-Antarctic. We hypothesized that locally endemic cryptic species will be found across the distribution of these direct-developing limpets in the sub-Antarctic. Location: The sub-Antarctic coasts of the Southern Ocean including South America, the Falkland/Malvinas, South Georgia, Kerguelen and Macquarie Islands. Methods: Multi-locus phylogenetic reconstructions, mtDNA time-calibrated divergence time estimations and population-based analyses of Siphonaria populations were used at the scale of the Southern Ocean. Results: We resolve two widely distributed lineages of Siphonaria (S. lateralis and S. fuegiensis) across the sub-Antarctic. MtDNA divergence time estimates suggest that they were separated around 4.0 Ma (3.0 to 8.0 Ma). Subsequently both species followed different evolutionary pathways across their distributions. Low levels of genetic diversity characterize the populations of both species, reflecting the role of Quaternary glacial cycles during their respective demographic histories, suggesting high levels of dispersal among geographically distant localities. Main conclusions: Siphonaria lateralis and S. fuegiensis constitute sister and broadly co-distributed species across the sub-Antarctic. Unexpected transoceanic similarities and low levels of genetic diversity in both these direct-developing species imply recurrent recolonization processes through long-distance dispersal to isolated sub-Antarctic islands. For such groups of Southern Ocean invertebrates, rafting may be more effective for long-distance dispersal than a free-living planktotrophic larval stage. This biogeographical model may explain why many marine species lacking a dispersal phase exhibit broad distributions, low genetic diversity and low population structure over thousands of kilometres.
Keywords: antarctic circumpolar current; direct developers; long-distance dispersal; oceanic biogeography; pulmonate; rafting; siphonaria; sub-antarctic